2022
DOI: 10.3390/ani12233297
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Functional Properties of Spray-Dried Porcine Plasma in Gilthead Seabream (Sparus aurata) Fed Low Fish Meal Diets

Abstract: Blood by-products are an untapped source of high-quality ingredients for aquafeeds, containing a broad variety of cytokines, hormones, growth factors, proteins, bioactive peptides, and amino acids. The effects of the spray-dried porcine plasma (SDPP), a type of processed animal protein on several immune parameters, were evaluated in sea bream using ex vivo and in vitro assays. In this study, fish were fed with two isoproteic, isolipidic, and isoenergetic diets: control diet (7% fish meal, FM) and SDPP diet (2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…Under certain situations, the skin mucus’s antioxidant capacity is promoted to protect the mucosal surface from oxidative attack, either due to environmental stress ( 91 , 92 ) or skin disorders ( 93 ). Due to the lack of oxidative challenging situations, we hypothesize that the dietary yeast supplementation promoted sentinel antioxidant defensive processes rather than activating response stress by reactive oxygen species (ROS) presence, which is in agreement with other studies focused on functional feeds ( 30 , 32 ). In addition, skin transcriptomics did not reflect responses linked to oxidative damage but to the downregulation of several genes involved in oxidative phosphorylation, which is the main metabolic ROS producer in cell metabolism ( 94 , 95 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Under certain situations, the skin mucus’s antioxidant capacity is promoted to protect the mucosal surface from oxidative attack, either due to environmental stress ( 91 , 92 ) or skin disorders ( 93 ). Due to the lack of oxidative challenging situations, we hypothesize that the dietary yeast supplementation promoted sentinel antioxidant defensive processes rather than activating response stress by reactive oxygen species (ROS) presence, which is in agreement with other studies focused on functional feeds ( 30 , 32 ). In addition, skin transcriptomics did not reflect responses linked to oxidative damage but to the downregulation of several genes involved in oxidative phosphorylation, which is the main metabolic ROS producer in cell metabolism ( 94 , 95 ).…”
Section: Discussionsupporting
confidence: 89%
“…The skin and its exuded mucus present a similar multifactorial behavior against the environment ( 26 ), and due to their direct contact with the aquatic environment, play a principal role in protection ( 27 ). An example of this involvement is the production of a specialized mucus layer with a wide range of physical and biochemical defensive components ( 28 , 29 ), which may be modulated through several factors, including dietary supplementation ( 30 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, it seemed to be influenced more by the immunostimulatory effect of SDPP. In another study on sea bream (Sparus aurata), SDPP supplementation at 5% demonstrated positive effects on growth, systemic immunity, and the antibacterial capacity of mucus, suggesting its potential as a functional ingredient in low fish meal aquafeeds [149].…”
Section: The Additive Of Sdap To Aquatic Animals' Dietmentioning
confidence: 98%
“…Currently, extrusion, emulsification, and spray drying are well-established techniques [16]. Spray-dried porcine plasma (SDPP) is highly regarded as a potential substitute for antibiotics, as it effectively enhances growth and boosts immunity [17]. In the present systematic review and meta-analysis, we compiled and analysed every piece of data ever collected regarding the likely immunological response and microbiota composition changes resulting from spray-dried porcine plasma, which may affect antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%